RE-SIGNIFIKASI RITUAL LOKAL MELALUI 3R DALAM SENI PERTUNJUKAN - Ni Nyoman Yuliarmaheni; Agil Pramudya Wardana; Putri Novalita (Universitas Negeri Makassar, 2025)
This article examines the re-signification of local rituals in Nyawer Manten Pari and Ngalang. It employs a comparative qualitative approach combining autoethnography and practice-led research through the 3R framework: revisiting, re-questioning, and reinterpreting. The findings show that both works transform local ritual into artistic, ecological, and social knowledge rather than merely an object of representation. The article also argues that 3R offers a methodological contribution to practice-based performing arts research grounded in local knowledge.